English : English - Liana Putri; Muhammad Mugni Assapari (ELP (Journal of English Language Pedagogy), 2025)
In a globalized world, English proficiency is essential for academic and professional success, significantly influencing educational and economic opportunities. Speaking skills are pivotal in language learning, serving various cultural and social functions in daily life. This study investigates the impact and factors influencing the effectiveness of Task-Based Speaking Activities in enhancing English speaking skills among MTS Al Ittihad students. Utilizing a quantitative research approach, this quasi-experimental design examined learners' speaking proficiency before and after implementing Task-Based Speaking Activities. Results indicate a marked improvement in students' speaking skills, with mean scores rising from 50.54 (pre-test) to 74.46 (post-test). Hypothesis testing further supports this finding, revealing a significant value of 0.00 (p < 0.05), demonstrating the effectiveness of Task-Based Speaking Activities on learners' proficiency. Initial assessments highlighted challenges in vocabulary, grammar, fluency, and pronunciation, emphasizing the need for innovative teaching strategies. The observed improvements underscore the activities' success in engaging students and enhancing their language comprehension and communication abilities.